PERSEPSI SITUATIONSHIP PADA DEWASA AWAL YANG MENGALAMI QUARTER-LIFE CRISIS - Eka Setiawati; Friska Berliana Berliana; Lita Rasonia Saragih; Tasya Salsabila; Dotor Hartaty Silaban; Fadhillah Salsabila Putri; Taqiyah Anasa Irsyah; Rifa Mulyani; Risydah Fadilah; Suaidah Lubis; Raja Bob Ridwan (Universitas Negeri Medan, 2026)
This study aims to explore and understand the perception of situationship in young adults experiencing a quarter-life crisis. The method used is a qualitative approach with a phenomenological design to determine the subjective experiences and perceptions developed by respondents. In this study, respondents were selected using a purposive sampling technique, with the following criteria: (1) aged 21–40 years, (2) currently experiencing or having experienced a situationship for at least three months, (3) experiencing signs of a quarter-life crisis, and (4) willing to participate in in-depth interviews. The number of participants was determined based on the principle of data saturation, namely when no new themes were found from the data collection process, amounting to 3 respondents. The results show that young adults experiencing a quarter-life crisis view situationship as a relationship without clear official status that is emotional and often used as a form of escape from life's pressures and uncertainties. In addition, those experiencing situationship also tend to be ambivalent. On the one hand, respondents feel comfort, relief, and emotional closeness. On the other hand, this relationship also causes anxiety, uncertainty, emotional confusion, and insecurity, especially when emotional expectations between the two parties are not balanced. This situation has the potential to cause negative psychological effects, such as anxiety and discomfort, in respondents experiencing a quarter-life crisis if not managed properly. Overall, this study provides an in-depth understanding of young adults' perceptions and experiences of situationship in the context of a quarter-life crisis.